Phoenician Mortuary Practice in the Iron Age I – III (ca. 1200 – ca. 300 BCE) Levantine “Homeland - Dixon, Helen M.; University of Michigan. (2013)
distinctions in material culture reflective of a city-based model of Phoenician identity. Instead, a significant degree of variation is evident in individual cemeteries, indicating that most Iron I-III period Phoenicians wished to signal not political allegiance or ethnic identity, but other aspects of their social identities in death. On the other hand, innovative Iron III practices shared by individuals across this territory willing to expend extensive resources on burial may point to the creation of a new “elite” identity or affiliation under Achaemenid influence.
Dissertation (Ph.D.)--University of Michigan.
Includes bibliographical references.
distinctions in material culture reflective of a city-based model of Phoenician identity. Instead, a significant degree of variation is evident in individual cemeteries, indicating that most Iron I-III period Phoenicians wished to signal not political allegiance or ethnic identity, but other aspects of their social identities in death. On the other hand, innovative Iron III practices shared by individuals across this territory willing to expend extensive resources on burial may point to the creation of a new “elite” identity or affiliation under Achaemenid influence.
distinctiveness. The study begins with a reassessment of inscriptions relating to Phoenician mortuary practice thought to date to the Iron I-II (Chapter II) and Iron III/Persian – Hellenistic (Chapter III) periods. The literary sources for Phoenician mortuary practice are then addressed, namely the Biblical (Chapter IV) and classical texts(Chapter V). This textual corpus is finally supplemented with a discussion of the burial database and mortuary landscapes of the Iron I-III period Levantine homeland (Chapter VI). All of this material is incorporated into a discussion of the treatment of the dead as a stage for Phoenician meaning-making in the Iron I-III periods (Chapter VII). Previous scholarship on Phoenicians has emphasized their city-based political allegiances on the one hand, and relatively uniform material culture on the other. But an examination of the Phoenician mortuary record indicates no expected regional
This dissertation examines the mortuary practices of the Iron Age I-III Levantine Phoenicians to document and analyze material expressions of social identity. The history of the Levantine Phoenicians has long been told from the perspective of their neighbors – via the texts of the Hebrew Bible, Greek and Roman authors, and inscriptions from Western Phoenician and Punic “colonies.” While extensive excavation is not possible in the most significant Phoenician cities (e.g. Byblos, Sidon, Tyre), a significant number of Iron Age burials found outside settlement boundaries have been explored or excavated since the 1850s. This project catalogs all burials known from the Phoenician “homeland” (coastal southern Syria, Lebanon, and northern Israel), offering a substantive contribution to a social history of these Phoenicians in the earliest periods of their cultural
Keywords: Phoenicia.; Iron Age Levant.; Phoenician Burials.; Mortuary Archaeology.